Output Feedback-Based Fuzzy Event-Triggered Synchronization Control for Nonlinear Multiagent Systems Under DoS Attacks - Xiaoru Lan; Limin Hou (IEEE Access)
This article studies the fuzzy event-triggered synchronization control problem for nonlinear multiagent systems (NMASs) under denial-of-service (DoS) attacks and unmeasured states. First, to estimate the leader’s system matrix and state under DoS attacks, a novel distributed secure estimator is constructed. Second, fuzzy logic systems (FLSs) are applied to approximate unknown dynamics, and a fuzzy state observer is proposed to estimate unknown states of NMASs. To save the data transmission and communication resources, an event-triggered mechanism (ETM) is employed to the controller design. Then, based on the developed distributed secure estimator and fuzzy state observer, an output feedback based fuzzy event-triggered synchronization control approach is proposed by utilizing backstepping technology. It is proven that all the signals are bounded and synchronization tracking is achieved. At last, a simulation example is provided to demonstrate the results achieved.